PERAN ORANG TUA ASUH DALAM MEMBINA KECERDASAN SPIRITUAL PADA ANAK DIDIK DI PANTI ASUHAN SULAIMAN DAHLAN JENANGAN PONOROGO. - Laili Nailul Muna; Nurul Iman; Wahyudi Setiawan (TARBAWI:Journal on Islamic Education, 2018)
This research is based on the guidance of the spiritual intelligence of the students in Sulaiman dahlan orphanage. Spiritual intelligence is influenced by several things one of them from how education or teaching done by parents, (in the discussion of this thesis is foster parents). This study aims to describe: 1) The efforts of foster parents in fostering the spiritual intelligence of students in the orphanage sulaiman dahlan. 2) The results achieved by foster parents in fostering spiritual intelligence protégé sulaiman dahlan. 3) What are the supporting factors and inhibiting factors in the effort to nurture the spiritual intelligence of students in the orphanage sulaiman dahlan. This research is a descriptive research with qualitative research approach. The subjects of this study were the head of the orphanage, foster parents, several alumni, and some santri. Data collection was done by observation method, structured interview, and documentation. Researchers are the main instruments in conducting research assisted by observation guides, interview guides, and documentation guidelines. Techniques used in data analysis are data display, data reduction and conclusion. The results of this study indicate that: 1) The role of foster parents in fostering the spiritual intelligence of students cover morale and material support. They educate and give direction at all times to their students. In addition they also facilitate students to develop the potential, according to each talent, by bringing teachers who are experienced in the field and include children in every moment that is able to develop its potential. 2) The results achieved from the guidance of spiritual intelligence include changes in attitude and morals of children before and after being in the orphanage, they also have the spirit of learning and awareness to memorize al-qur'an, and the spirit of learning is high. 3) Supporting factors that are adequate facilities and the opportunity as well as support to further develop the intelligence and inhibiting factors of spiritual intelligence of students in the orphanage sulaiman dahlan, self-motivation, the role of family environment, community environment, and school environment.